The preparation of chitosan/PVA/zeolite electrospun composite nanofibrous membrane for heavy metal removal application / Umma Habiba - Umma, Habiba (2016)
Water is being polluted in many different ways. Moreover, existing water and wastewater treatment processes are going to exceed the limit for supplying sufficient water quality to meet the demands. More efficient water treatment membrane made of polymeric materials from renewable resources are necessary. Chitosan is a biopolymer which is very well known for its biodegradability, nontoxicity, biocompatibility etc. As it is a partially deacetylated derivative of chitin, it behaves as polycationic in nature. Producing chitosan nanofiber via electrospinning is a challenge due to its polycationic behavior. In addition, limited solubility of chitosan and protonation of amino group decrease the electrospinnability of chitosan. To increase the electrospinnability, it is necessary to increase the degree of deacetylation and decrease the protonation of chitosan. In order to reduce the protonation of chitosan in acidic medium and water, blending with other polymer like PVA is helpful as it make hydrogen bond with amino group. Zeolite is widely being used for water treatment because of its molecular sieve structure. The objective of this study is to fabricate a novel chitosan/PVA/zeolite nanofibrous composite membrane via electrospinning process. Firstly, crude chitosan was hydrolyzed with NaOH for 24 hours to make the electrospinning feasible. Hydrolyzed chitosan was analyzed by FTIR. Consequently, degree of deacetylation and molecular weight of hydrolyzed chitosan was calculated. Analysis over hydrolyzed chitosan resulted in increase of degree of deacetylation. This will ease the electrospinning process. Next, 7 wt.% of hydrolyzed chitosan solution made by dissolving in 90% conc. acetic acid was blended with 8wt% of aqueous polyvinyl alcohol solution. Five electrospinning dope with the different weight ratio of chitosan/PVA was prepared, those are 50:50, 60:40, 70:30, 80:20 and 90:10. The electrospinning dope was then loaded in a syringe for electrospinning. Morphology of the electrospun products were studied by FESEM. FESEM analysis showed that chitosan/PVA with 50:50 weight ratio gave defect-free nanofibrous mat. Where, higher chitosan content in the blend solution lead to poor nanofiber. Therefore, 50:50 weight ratio of chitosan/PVA was selected as the polymer matrix for zeolite. Then, 1 wt % of zeolite was added to the blend solution followed by electrospinning process. The structure and elemental studies on the electrospun composite nanofiber was characterized with field emission scanning electron microscopy, X-Ray diffraction, Fourier transform infrared spectroscopy, swelling test and adsorption test. The result showed that chitosan/PVA/zeolite nanofibrous composite was successfully produced via electrospinning process. From the FESEM result, finer, beads free nanofiber with homogeneous size was electrospun. Fourier Transform Infrared spectroscopy test shown a strong bond between chitosan and zeolite. X-Ray diffraction spectra also showed strong interaction of chitosan and zeolite. Zeolite loses its crystallinity due to strong bonding with chitosan molecules. Swelling test showed no change in weight after immersing in distilled water, acidic and basic medium for 20 days. The isotherm models showed that the Langmuir model described the equilibrium data of Cr (VI), Fe (III) and Ni (II) adsorption. Adsorption capacity of the nanofiber was unaltered after 5 recycling runs which indicate the reusability of the chitosan/PVA/zeolite nanofibrous membrane.